Социально-экономическая эффективность: опыт США: Ориентир на глобализацию - Кириченко Э. В. Элина Всеволодовна; Онищенко И. С.; Лебедева Е. А. Евгения Александровна; Раннева Н. А.; Рубцов Б. Б.; Кондратьев В. Б. (Москва, Наука, 2002)
Авт. указ. на обороте тит. л.